The Tinged Parchment-Cutaneous Mastocytosis - Bajaj Anubha (International Journal of Global Health, 2023)
A clinical image and brief discussion of cutaneous mastocytosis describe presentation, dermoscopy, and diagnostic clues. The note underscores when to evaluate for systemic involvement.